EFFECTIVENESS OF PRODUCTIVE ZAKAT FUNDS IN EVELOPMENT MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) IN SOUTH KALIMANTAN - Mahfuzah, Annisa; Maulida, Atika Zahra; Asyahri, Yusuf; Sayyid, Annisa; Hafizah, Hafizah; Khairina, Nadia (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
MSMEs play a crucial role in driving economic growth and reducing poverty in South Kalimantan. Despite their significant contribution, this sector still faces various obstacles, including access to financing. Effective management of productive zakat funds has the potential to become an alternative funding instrument to address these challenges, while simultaneously increasing MSMEs empowerment and reducing poverty. Therefore, this study aims to assess the effectiveness of productive zakat management in supporting MSMEs and optimizing their impact on the regional economy. This study uses a descriptive-analytical approach in fieldwork. The method used is a combination of qualitative and quantitative methods. The population in this study were all beneficiaries of productive zakat funds through the digital economic empowerment programs Micropreneur 2023, Zmart 2023, and Biofloc system fisheries cultivation, as well as laying hen farmers, with a population of 160 beneficiaries and a research sample of 74 respondents accompanied by 8 informants. The research results show that the management of productive zakat through various programs implemented by Baznas in South Kalimantan has been running well, with most indicators achieving a high level of effectiveness. Two indicators, namely target success and program satisfaction, were declared effective, while the levels of input and output, as well as program achievement, were deemed quite effective. These findings indicate that productive zakat management plays a significant role as an alternative funding instrument in supporting MSMEs, while also making a real contribution to improving the community's economy by channeling funds to mustahik (recipients of zakat) who run MSME-scale businesses.